2002
DOI: 10.1890/0012-9658(2002)083[2037:cpahso]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Coyote Predation and Habitat Segregation of White-Tailed Deer and Mule Deer

Abstract: Predation has been proposed as a major factor maintaining segregation among species of ungulates, but predator-prey interactions have not been observed to test this idea directly. Here, observations of coyote (Canis latrans) packs hunting deer are used to show that mule deer (Odocoileus hemionus), which typically stand high on slopes and on rugged terrain, increased both their risk of being encountered and attacked by coyotes by standing low rather than high on slopes. The risk incurred at certain heights was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(77 citation statements)
references
References 50 publications
3
73
0
Order By: Relevance
“…WVC occurrence is shaped by an interaction of habitat selection, population abundance, and road variables (Forman et al 2003, Seiler 2005, Gunson et al 2011. Moreover, previous work in our study area by Lobo and Millar (2013) show that WVCs by these two deer species tend to occur in the same area, and Lingle (2002) showed that Odocoileus spp. overlap for foraging and movement in an area nearby our study site.…”
Section: Wildlife-vehicle Collision Datamentioning
confidence: 56%
“…WVC occurrence is shaped by an interaction of habitat selection, population abundance, and road variables (Forman et al 2003, Seiler 2005, Gunson et al 2011. Moreover, previous work in our study area by Lobo and Millar (2013) show that WVCs by these two deer species tend to occur in the same area, and Lingle (2002) showed that Odocoileus spp. overlap for foraging and movement in an area nearby our study site.…”
Section: Wildlife-vehicle Collision Datamentioning
confidence: 56%
“…The effect of habitat characteristics on escape behaviour may, however, be different even in closely related species of deer. When approached by coyotes, mule deer (Odocoileus hemionus) escape uphill and towards slopes whereas white-tailed deer (Odocoileus virginianus) flee downhill and away from slopes (Geist, 1981;Lingle, 2002). These two species also differ in their initial response to a threat.…”
Section: Mammalsmentioning
confidence: 99%
“…Coyotes prey on mule deer, especially young animals in their first year (fawns; Lingle 2000;deVos et al 2003;Pojar and Bowden 2004), and female deer (does) choose to hide their newborn fawns in relatively safe habitats (Long et al 2009). When coyotes are present, mule deer also tend to move from preferred feeding habitats into safer habitats, at a cost of lower feeding rate (Lingle 2002; see also LaundrĂ© et al 2001). Coyotes might indirectly benefit plant species that deer prefer by reducing the number of deer and their feeding rates.,.…”
Section: Introductionmentioning
confidence: 99%